Current Concepts of Contemporary Expandable Lumbar Interbody Fusion Cage Designs, Part 2: Feasibility Assessment of an Endplate Conforming Bidirectional Expandable Interbody Cage - CHENG, BOYLE C. (Int J Spine Surg, 2020)
BACKGROUND: Expandable cages that allow for bidirectional expansion, in both height and width, may offer benefits over traditional expandable cages or static cages. Effective stiffness must also be considered, as implants with exceedingly high stiffness may increase subsidence risk and reduce graft loading. METHODS: A retrospective case series of 7 patients were assessed with computed tomography (CT) scan at the final 1-year follow-up to evaluate the interbody fusion and configuration of the expandable cage related to the endplates within the intervertebral space. CT scans were reformatted using cage's tantalum markers as fiducials for single-plane orientation for each intervertebral cage. Device height and width at maximum in situ expansion was measured at its anterior and posterior aspects to evaluate implant deformation. The new bone volume within each cage was measured from the same CT scan data sets and by the Bridwell classification of interbody fusion. RESULTS: The average difference between medial and lateral height measurements was 1.82 mm (±1.08) at the device's anterior aspect and 1.41 mm (±0.98) at the posterior aspect. The average difference between medial and lateral heights was 18.55% (±9.34) anteriorly and 15.49% (±9.24) posteriorly. There was a successful fusion in all 7 patients, as evidenced by measurable bone volume in the center of each interbody cage with an average of 586.42 mm(3) (±237.06). CONCLUSION: The authors demonstrated the feasibility of successfully using bidirectionally expandable multimaterial cages to achieve interbody fusion. These composite open-architecture cages were found to conform to each patient's endplate configuration. The authors' observations support the concept of material selection impacting the effective construct stiffness. The design investigated by the authors provided sufficient anterior column support and successful fusion in all patients. LEVEL OF EVIDENCE: 4.